Penataan Struktur Hukum Hak Atas Tanah dalam Rangka Keadilan dan Investasi - Rosmidah, Rosmidah; Hosen, M.; Sasmiar, Sasmiar (Magister Kenotariatan, Universitas Jambi, 2023)
Land issues in Indonesia are increasingly complex, throughout the 63 years of the UUPA as the main land regulation it has not been able to realize justice for land. The investment climate and development complexity caused by the plurality of social structures and overlapping land policies, especially since the issuance of the Job Creation Law, has now become Law no. 6 of 2023 concerning the stipulation of PERPU Law NO. 2 of 2022 concerning Job Creation becoming a law has a great influence on land law. The problem is how the political development of land law in Indonesia is developed and how to create a legal structure for control, ownership, use and exploitation of land that can fulfill the principles of justice and investment. This research is normative research with a statutory regulatory approach, a historical approach and a conceptual approach. The results of the research are that 1. the current development of land law politics tends to ignore the principles contained in the UUPA and deny agrarian reform. This is reflected in various land law regulations which give rise to ambiguity and multiple interpretations because the issuance of sectoral laws is driven by economic growth and investment and the emergence of various land conflicts at the empirical level 2. The legal structure of control, ownership, use and utilization of land can realize justice if it continues to pay attention to the principles enshrined by the UUPA, including the maximum use of land for the prosperity of the people. Suggestions, there is a need to review land law policies in the context of balancing control, ownership, use and utilization of land between providing justice for the community and facilitating investment.